Aboriginal and Torres Strait Islander art - Stolte, Gretchen M., author.
1 online resource (xvi, 229 pages)
Keywords: Aboriginal and Torres Strait Islander Art explores the effects of Queensland government policies on urban First Nation artists. While such art has often been misinterpreted as derivative lesser copies of true' Indigenous works, this book unveils new histories and understandings about the mixed legacy left for Queensland Indigenous artists. Gretchen Stolte uses rich ethnographic detail to illuminate how both Aboriginal and Torres Strait Islander artists understand and express their heritage. She specifically focuses on artwork at the Aboriginal and Torres Strait Islander art studio in the Tropical North Queensland College of Technical and Further Education (TNQT TAFE), Cairns. Stolte's ethnography further develops methodologies in art history and anthropology by identifying additional methods for understanding how art is produced and meaning is created.